Brokering Peace in Nuclear Environments : U.S. Crisis Management in South Asia - Moeed Yusuf (California Stanford University Press, 2018)
This text theorizes third party mediation in crises between regional nuclear powers. Its relevance flows from two of the most significant international developments since the end of the Cold War: the emergence of regional nuclear rivalries; and the shift from the Cold War's bipolar context to today's unipolar international setting.
Include Index
Keywords: a